Does shared group identification lead to group creativity? Group regulatory focus as a moderator - Lee, Eun Suk; Park, Tae Youn; Paik, Yonjeong (Journal of Applied Social Psychology, 2019)
Regarding the effect of identification on creativity in groups, two theoretical views compete. One view emphasizing group-welfare motives underlying identification proposes a positive identification–creativity relationship in groups because members sharing high group identification are motivated to engage in behaviors that they believe are optimal for their group, including those that depart from the group's status quo, thus resulting in enhanced group creativity. The other view highlighting affiliative motives underlying identification, in contrast, posits a negative identification–creativity relationship in groups because highly identified members are motivated to engage in behaviors that certify their belongingness in the group, that is, behaviors that conform to the existing group norms and status quo, which constrains the group's potential for creativity. This study aims to reconcile these competing perspectives by invoking regulatory focus theory. Drawing on the notion that group identification effects rely on the content of group identity that the identification is based on, the authors suggest that group regulatory focus, as a critical group identity content, moderates the identification–creativity relationship in groups; the relationship is positive when the group's regulatory focus is highly promotion-oriented, whereas it is negative when the group's regulatory focus is highly prevention-oriented. Analyzing data from 65 workgroups in a cosmetics company in Korea, the authors show evidence that the identification–creativity relationship is positive in groups with a high promotion focus. The prediction regarding the prevention–focus moderation effect is not supported. The implications of the findings for both theory and practice are discussed.